Nanotechnology through the lens of law: Asia and beyond - Karim, M.E. (2014)
Nanotechnology, the science of using materials at the atomic or molecule scale, is the next wonder after internet. Its virtually limitless prospects compel the government, research firms and business ventures around the world to invest huge amount for its commercial application. United Nations is convinced nanotechnology can be used to achieve the Millennium Development Goal and it can improve the quality of life 5 billion people of developing countries. More than 2000 consumer products are already in the market and ILO predicts that by 2020, 20% of the products will be nanotech-enabled. However, there are some tensions too regarding the risks and safety issues of nanoparticles and how the legal framework and institutions will react in such situation. To many, due to identical fibrous shape and chemical property, nanomaterial is the next asbestos as it has some serious consequence on environment and human health. Gleaming and spell bound consumer products are conquering the market very fast beating the reactions of regulators. This is a matter of serious concern that there is no specific and comprehensive regulation both in national or international level to handle the possible environment and human health threats, except some voluntary or soft law tools. In this backdrop, this paper aims to focus on ongoing environment and health concerns relating to nanotechnology and the possible legal responses against such concerns within the existing international and national regulatory framework. Such a discussion may portray an overview of the legal and regulatory aspects of nanotechnology to the stakeholders.